How could you help me? Children's voices on violence in child welfare files: A thematic analysis - Sara Quarles van Ufford; Ulla-Karin Schön; Maria Heimer; Hanna Linell (Child Protection and Practice)
Background: A significant number of children experience violence, frequently from parents or other caregivers. Yet, many of these children lack access to community support, largely due to the challenges they face in disclosing abuse. Even when children do disclose abuse, it does not necessarily lead to their receiving the help needed. Recognizing children as epistemic subjects is essential both for ensuring their access to adequate support and for advancing knowledge about child abuse. Objective: This study aimed to explore children's voices on violence in child welfare files to enhance our understanding of their experiences of violence. Participants and setting: The sample consisted of 120 children who provided abuse information in Swedish child welfare investigations into physical and sexual abuse. Method: Data were collected from child welfare files and analyzed qualitatively using thematic analysis. Results: Six themes were identified—acts of violence, emotions, context, disclosure, agency, and abuse dynamics—all of which informed the overarching theme: Children's voices highlight violence as a specific problem characterized by power and control dynamics that significantly impact their lives. Conclusions: The collective findings indicate that mechanisms of violence extend beyond physical acts, emphasizing the need for Child Welfare Services (CWS) to recognize child abuse as a distinct issue characterized by dynamics of power and control. These dynamics significantly affect children's health and their capacity to assert their own interests. Failure to address these aspects risks underestimating the severity of the violence and impeding the provision of adequate support.